1991
DOI: 10.1177/095632029100200102
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine-Mediated Inhibition of Rabies Virus Infection in vitro and in Rat Brain

Abstract: SummaryThis report describes the effect of the dissociative anaesthetic ketamine, a non-competitive antagonist of the N-methyl-D-aspartate (NMDA) receptor, on the infectivity of the neurotropic rabies virus, in neuronal culture systems and in vivo. produced an approximate 10Q-1000-fold decrease in the production of rabies virus in neuronal cell cultures. Rabies virus infection was also inhibited in non-neuronal cell lines (Baby Hamster Kidney fibroblasts) but the inhibitory effects appeared better expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 33 publications
0
23
0
2
Order By: Relevance
“…Cortical neurons were prepared in 24-well poly-Lornithine-coated (3 ~tg/ml, Sigma) dishes from 15-day-old rat embryos as previously described (Lockhart et at., 1991) with the following changes. On the fourth day in culture 5-fluoro-2"-deoxyuridine (10 ~tg/ml) and uridine (25 gg/ml) were added to the F-10 medium for 24 h to control non-neural cell proliferation.…”
Section: Methodsmentioning
confidence: 99%
“…Cortical neurons were prepared in 24-well poly-Lornithine-coated (3 ~tg/ml, Sigma) dishes from 15-day-old rat embryos as previously described (Lockhart et at., 1991) with the following changes. On the fourth day in culture 5-fluoro-2"-deoxyuridine (10 ~tg/ml) and uridine (25 gg/ml) were added to the F-10 medium for 24 h to control non-neural cell proliferation.…”
Section: Methodsmentioning
confidence: 99%
“…The findings indicate that caution should be taken before subjecting future human rabies patients to therapy with ketamine on the basis of the previous experimental work (15,16,20). There have been at least four patients treated with ketamine after the survivor received ketamine in 2004, and all of these patients progressed to fatal outcomes (7).…”
mentioning
confidence: 99%
“…The events in rabies virus infection that lead to CNS disease and a fatal outcome are still not well understood (6). Studies with rat cortical neurons and with a rat model suggested the possibility that the noncompetitive Nmethyl-D-aspartate acid (NMDA) antagonists ketamine and MK-801 might be effective therapeutic agents for human rabies (15,16,20) and that ketamine inhibits viral RNA genome transcription (15). Consequently, a working group recommended that ketamine be considered for the therapy of human patients with rabies (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recommendation for therapy with ketamine was based on animal work that was performed at the Institut Pasteur in Paris, France, in the early 1990s [7]. Like current therapies for cancer, HIV infection and chronic hepatitis C infection, it was felt that a combination of therapies might be effective where specific therapies had failed in the past.…”
mentioning
confidence: 99%